2009
DOI: 10.1007/s12355-009-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Post harvest quality deterioration in sugarcane under different environmental conditions

Abstract: Post harvest changes in the juice quality parameters in relation to storage time were investigated in three sugarcane genotypes varying in maturity behaviour viz.CoJ83

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
5
14
0
1
Order By: Relevance
“…The chemical treatment was thus effective in minimizing plant and microbial-linked inversion losses in harvested sugarcane. Bhatia et al (2009) reported increases in reducing sugars in juice after storage of cane. The extensive formation of reducing sugars after harvest is probably due to enhanced activity of invertase(s) of plant and microbial origin (endogenous and exogenous) and increased respiratory activity in the harvested stalk.…”
Section: Decline In Sucrose (Pol% Juice)mentioning
confidence: 98%
“…The chemical treatment was thus effective in minimizing plant and microbial-linked inversion losses in harvested sugarcane. Bhatia et al (2009) reported increases in reducing sugars in juice after storage of cane. The extensive formation of reducing sugars after harvest is probably due to enhanced activity of invertase(s) of plant and microbial origin (endogenous and exogenous) and increased respiratory activity in the harvested stalk.…”
Section: Decline In Sucrose (Pol% Juice)mentioning
confidence: 98%
“…This may be due to over mature condition of CoJ83 at that time. Bhatia et al (2009) earlier reported that early maturing cultivar on becoming over mature deteriorated much faster as compared to mid maturing variety during late crushing season. However, inspite of higher percentage increase in dextran content, the dextran content in juice remained less in CoJ83 in comparison to CoS8436 (Table 2).…”
Section: Effect Of Days Of Incubation On Dextranase Productionmentioning
confidence: 89%
“…Highest content of dextran was found in variety CoS8436, followed by CoH119, CoJ88 and CoJ83. According to Solomon et al (2003) and Bhatia et al (2009) the dextran content varied with cane variety. Irrespective of variety, dextran content increased with increase in storage period.…”
Section: Effect Of Days Of Incubation On Dextranase Productionmentioning
confidence: 99%
“…The degradation of sucrose might be caused by the acid invertase enzymes that are produced by a few yeast species in the preserved juice (Hanko & Rohrer, 2000). In previous studies, several microorganisms (e.g., lactobacillus, yeast and molds) were also isolated, which were responsible for the spoilage of sugars and caused discoloration and the reduced the pH of SSJ (Bhatia, Uppal, Thind, & Batta, 2009;Ramachandran et al, 2017;Rao et al, 2012). Sucrose was converted into dextran though dextransucrase enzyme from Leuconostoc spp (Kin & Robyt, 1995).…”
Section: Sugars Concentration In the Presence Of Chemical Preservatmentioning
confidence: 99%